Relevance and Reason Relations. (29th December 2016) - Skovgaard‐Olsen, Niels; Singmann, Henrik; Klauer, Karl Christoph
Abstract: This paper examines precursors and consequents of perceived relevance of a proposition A for a proposition C. In Experiment 1, we test Spohn's (2012) assumption that ∆P = P(C|A) − P(C| A) is a good predictor of ratings of perceived relevance and reason relations, and we examine whether it is a better predictor than the difference measure (P(C|A) − P(C)). In Experiment 2, we examine the effects of relevance on probabilistic coherence in Cruz, Baratgin, Oaksford, and Over's (2015) uncertain "and‐to‐if" inferences. The results suggest that ∆P predicts perceived relevance and reason relations better than the difference measure and that participants are either less probabilistically coherent in "and‐to‐if" inferences than initially assumed or that they do not follow P(if A, then C) = P(C|A) ("the Equation"). Results are discussed in light of recent results suggesting that the Equation may not hold under conditions of irrelevance or negative relevance.